Half of resources in threatened species conservation plans are allocated to research and monitoring - Rachel T. Buxton (Nature Portfolio, 2020)
How to best allocate limited resources for conserving imperilled species is a difficult challenge. Here the authors analyse data on over 2000 threatened species from USA, Australia, and New Zealand, finding that on average half of the budget is allocated to research and monitoring. Species with higher budget allocation to research and monitoring tend to have poorer recovery outcomes.